PROMOTION OF SELF-CONFIDENCE OF A PROSPECTIVE MUSIC TEACHER AS A PERFORMER - Rauduvaitė, Asta; Bi, Guanhua (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Self-confidence is a key factor that influences stage performance. To form a positive state while performing on the stage, self-confidence becomes the most important aspect, as it is one of the main guarantees of successful performing. However, in music teaching, many students lack self-confidence when performing, which in most cases hinders their performance results. The aim of the study is to reveal the peculiarities of promoting self-confidence of students as performers. A questionnaire and an interview with music education students were used to collect the data. The results of the questionnaire allow concluding that experience as a performer, physical and psychological preparation, and self-regulation are the three major factors influencing students’ lack of confidence during the performance. Additionally, the responses from the interview indicated other equally prominent and influential factors such as performing environment, practice level and stage experience. Lastly, the interviewed students proposed ways to boost self-confidence, which include gaining more music knowledge and improving their music skills, practicing harder and applying self-regulation.